Perioperative management of patients with Mucolipidosis II and III: Lessons from a case series. Issue 3 (12th December 2020) - Scott‐Warren, Victoria Louise; Walker, Rob
Abstract: Mucolipidosis (ML) II and III are complex lysosomal storage disorders characterized by progressive multisystem pathology which can pose challenges to the anesthetist and increase the risks associated with general anesthesia. We sought to review the management of patients with ML II and III undergoing anesthesia in our institution in order to better define recommendations for the preoperative assessment and optimization of these children. We further elected to analyze the conduct of anesthesia, intraoperative management, and perioperative complications that our patients had experienced in order to allow improved informed consent and anesthetic planning. We performed a retrospective examination of the medical notes of those patients who had undergone anesthesia in our institution to identify their clinical features, anesthetic technique, airway management, and perioperative complications. Five children underwent 11 episodes of anesthesia. Fiber‐optic or videolaryngoscopy was utilized in six out of seven intubations, with four out of seven requiring a change from the method initially chosen to enable intubation. Four of the five patients had an abnormal echocardiogram. Three patients had radiological evaluation of their cervical spine, with two demonstrating abnormalities. One patient had changes suggesting instability at the atlantoaxial junction. Children and babies with ML II and III present multisystem challenges to the anesthetist. Multidisciplinary planning and assessment, followed by a discussion of risk, should proceed any elective surgery. These complex children should undergo elective anesthesia delivered by an experienced (pediatric) anesthetist in an appropriate tertiary center with on‐site pediatric ENT and critical care support.